William Allen correspondence - Allen, William, active 1885-1886.
Letter by Allen (Sept. 25, 1886) answering queries concerning the Rotuman dialect of the island of Rotuma in the South Pacific, and forwarding a vocabulary he compiled to A. L. Pirrart.
Clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Allen, William, -- active 1885-1886 -- Correspondence; Pirrart, A. L. -- Correspondence; Rotuman language; Rotuma Island (Fiji) -- Languages